Business analytics: financial modelling and price management - Lee, Wei Han (Nanyang Technological University, 2024)
This project provides a comprehensive overview of Evoqua Water Technologies' strategic focus on the APAC region and the methodologies employed to optimize its business operations, while also addressing pertinent challenges encountered throughout. This project aims to optimize pricing strategies, streamline financial reporting processes, and leverage machine learning for customer segmentation. Through meticulous data preprocessing and implementation of Excel VBA and Power BI, Evoqua enhances operational efficiency and decision-making capabilities. Integration of machine learning algorithms facilitates customer segmentation and pricing optimization, driving sustainable growth and maintaining Evoqua's leadership position in the water treatment industry.